Análisis de planes estatales de intervención sobre el suicidio - Luna Tascón, Edwin Gerardo; Rodríguez Pabón, Diana; Sánchez Martínez, Nubia Rocío (Universidad y Salud, 2011)
In order to identify the most frequently strategies used for suicidal behavior intervention, a content analysis of 7 plans developed by states or nations to prevent suicidal behavior was carried out. 49 strategies were identified, from these 9 inductive categories emerged. Besides a classification of the strategies was done according to intervention object (directed to the physical or social context or to high risk people), intervention type (promotion, primary prevention, secondary prevention and tertiary prevention), and systems of the ecological model toward they are directed to (microsystem, exosystem, macrosystema, and all systems). It was established that most of the strategies are directed to: (a) acquiring information and generating suicide related knowledge; (b) improve the mental health offer processes and the detection and attention routes to suicide cases; (c) intervene the physical or the social environment; (d) develop primary prevention actions; and, (e) take part on the exosystem.